Redefining European security - Hodge, Carl Cavanagh (New York : Garland, 1999)
Redefining European Securityis a collection of essays concerned with changing perspectives on peace and political stability in Europe since the end of the Cold War, in both the "hard" security terms of military capacity and readiness and in the realm of "soft" security concerns of economic stability and democratic reform. European governments, the European Union, and the North Atlantic Treaty Organization are dealing with the fundamental problem of determining the very parameters of Europe, politically, economically, and institutionally. This book defines security as the efforts undertaken by national governments and multilateral institutions, beginning with the end of the Cold War and the reunification of Germany, to continue to protect European populations from acts of war and politically-motivated violence in light of the dissolution of the imminent political threat posed to Western Europe by the Soviet Union, 1945-1991 Together these essays assess the progress made in Europe towardpreventing conflict, as well as in ending conflict when it occurs, after the abrupt passing of a situation in which the source and nature of a conflict were highly predictable and the emergence of new circumstances in which potential security threats are multiple, variable, and difficult to measure. Contemporary Europe is a mixture of old and new, of arrested and accelerated history. Europe's governments and institutions have been only partly successful in meeting new security challenges, to a high degree because of failing unity and political will. "Yesterday, Europe only just avoided perishing from imperial follies and frenzied ideologies," wrote the late Raymond Aron in 1976, "she could perish tomorrow through historical abdication."
Introduction : Crucial problems of security in Europe / Gerhard Wettig -- European security between the "logic of anarchy" and the "logic of community" / John Baylis -- The revival of geopolitics in Europe / Heinz Magenheimer -- The economic elements of the European security order / James Sperling -- A separate peace? Economic stabilization and development and the new fault line of European security / Colette Mazzucelli -- Transnational threats and European security / Phil Williams and Paul N. Woessner -- France's security policy since the end of the Cold War / Axel Sauder -- France and the organization of security in post-Cold War Europe / Michael Meimeth -- Redefining European security : the role of German foreign policy / Klaus von Beyme -- Germany : is sound diplomacy the better part of security? / Carl Cavanagh Hodge -- Russia and European security / Paul Marantz -- The future of American Atlanticism / Gary L. Geipel -- The military aspects of European security / Edward M. Whalen -- Between ambition and paralysis : the European Union's Common Foreign and Security Policy and the war in the Former Yugoslavia / Andreas G. Kintis -- The OSCE : nonmilitary dimensions of cooperative security in Europe / Cathal J. Nolan -- Conclusion: Where Is Europe?
Includes bibliographical references (pages 349-361) and index.
Print version record.
eBooks on EBSCOhost
Keywords: National security -- Europe; Europe -- Defenses; World politics -- 1989-; Europe -- Défense.; Politique mondiale -- 1989-; TECHNOLOGY & ENGINEERING -- Military Science; HISTORY -- Military -- Other; Military readiness; National security; World politics; Europe; Since 1989